Evaluation of Depression and Anxiety in Coronary Artery Bypass Surgery Patients: A Prospective Clinical Study - Melike Elif Teker Açıkel (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: The aim of this clinical study is to determine the depression and anxiety levels in coronary artery bypass graft (CABG) surgery patients in the pre and postoperative periods. Methods: This clinical prospective study was done with 65 patients. Beck’s Depression Inventory (BDI) and Beck’s Anxiety Inventory (BAI) tests were performed in patients who had a diagnosis of coronary artery disease and were awaiting CABG surgery. These patients presented characteristic symptoms of anxiety and depression and BDI and BAI tests are important to assess these symptoms. Results: We found out that depression and anxiety levels were higher in the postoperative than in the preoperative period (P<0.001). Both anxiety and depression levels were increased significantly following CABG operation when compared with preoperative levels in all patients. Statistical correlation of depression and anxiety in different ages, genders, and professions were evaluated too, but we did not found a correlation between them (P>0.05). Conclusion: We suggest that good management of the psychological condition of cardiac surgery candidates, as well as post-bypass patients, will improve quality of life and cardiovascular outcomes in these patients.